Marine Bioactive Peptides II: Structure, Function, and Therapeutic Potential - Ovchinnikova, Tatiana V. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This second edition of the Special Issue "Marine Bioactive Peptides: Structure, Function, and Therapeutic Potential - II" published papers on up-to-date information regarding isolation, structural elucidation, functional characterization, and therapeutic potential evaluation of peptides isolated from marine organisms. Chemical synthesis and biotechnological production of marine peptides and their mimetics will also be a focus of this Special Issue. In addition, this Special Issue will publish new results arising from a peptidomic approach. 24 Papers were accepted and included in the first issue, which we published as a Special Issue book (https://www.mdpi.com/books/pdfview/book/1742). Following the success of the first Special Issue, as Guest Editor, I invite researchers in the field to contribute to the second edition entitled " Marine Bioactive Peptides: Structure, Function, and Therapeutic Potential - II] ".